Contestation of Islamic Law on Traditional Sharecropping in Rural West Java, Indonesia - Kusmayanti, Hazar; Kania, Dede; Riswadinata, Indra; Kim, Hyung-Jun (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
This study examines the contested legal status of traditional sharecropping contracts among Islamic scholars and religious leaders in rural West Java, Indonesia. The primary objective is to analyze how Islamic law governs these contracts both normatively and in practice and how relevant regulations function within the local context. Employing an empirical legal approach, the research relies on direct observation and analysis of legal behavior in society. Findings indicate that the rising value of land and labor has turned traditional sharecropping arrangements into symbols of economic inequality. Ideologically, the legitimacy of such contracts is debated among village groups with varying socio-religious orientations. This contestation reflects an ongoing process of rural Islamization and highlights emerging pragmatism. The increasing accessibility of global information via the internet enables rural communities to reinterpret Islamic legal norms and agricultural practices, illustrating their adaptive responses to socioeconomic change and technological advancement.